2010
DOI: 10.1111/j.1478-3231.2009.02127.x
|View full text |Cite
|
Sign up to set email alerts
|

Ad36 adipogenic adenovirus in human non-alcoholic fatty liver disease

Abstract: Ad36 seropositivity is not associated with a significant difference of IR in NAFLD patients, but is associated with a greater adiposity. Ad36 seropositivity is associated with a lower occurrence of NAFLD and bright liver, which, conceivably, is not directly mediated by IR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 27 publications
3
59
1
Order By: Relevance
“…In both cohorts, Ad36 infection was associated with significantly lower IHL ( Table 1). These findings agree well with a recent report of protection from nonalcoholic fatty liver disease (NAFLD) in Ad36 seropositive people (60). These findings suggest that Ad36 infection may protect individuals from impaired glucose tolerance (IGT) and HS, two key risk factors associated with type 2 diabetes and serious liver diseases.…”
Section: Experiments 3: Ad36 Is Associated With Better Glycemic Controsupporting
confidence: 92%
“…In both cohorts, Ad36 infection was associated with significantly lower IHL ( Table 1). These findings agree well with a recent report of protection from nonalcoholic fatty liver disease (NAFLD) in Ad36 seropositive people (60). These findings suggest that Ad36 infection may protect individuals from impaired glucose tolerance (IGT) and HS, two key risk factors associated with type 2 diabetes and serious liver diseases.…”
Section: Experiments 3: Ad36 Is Associated With Better Glycemic Controsupporting
confidence: 92%
“…Straight, discrete, and significant mutual linear relationships between insulin resistance, obesity, and severity of fatty liver involvement are reported, and the possibility that the Ad36 adenovirus can interfere in the pathogenesis of fat storage in hepatocytes with mechanisms different from those operating in adipose cells was suggested [13]. A higher prevalence of human adenovirus Ad36 antibodies seropositivity is present in obese people [34]; nonetheless, Ad36 seropositivity in our previous study is associated with a lower occurrence of NAFLD and bright liver in subjects with the same grade of obesity [43]. Moreover, Ad36 ?…”
Section: Introductionmentioning
confidence: 66%
“…The liver is assessed for size, contour, echogenicity, structure, penetration of the US beam, i.e., posterior beam attenuation and portal vessel wall distinction. The degrees of bright liver considered for statistical evaluation are classified by combining three subscale grades focused on echogenicity, beam penetration, and portal vessel wall distinction: grade 0 -normal or slightly reduced in comparison with right kidney echogenicity; grade 1 -slightly increased in comparison with right kidney echogenicity; grade 2 -clearly increased, with a decline in echo amplitude (i.e., posterior beam attenuation owing to the high reflectivity of the fat liver parenchyma); and grade 3 -markedly increased with a decline in echo amplitude and impaired portal vessel wall distinction, i.e., loss of echoes from the walls of the portal vein [13,43,[45][46][47]. All US procedures to be used for data analysis are performed and assessed by a single senior specialist (DC) not informed of any clinical detail including the Ad36 serological status and the previous US examination reports and results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 In addition, other studies using the Italian and the US children and adolescents demonstrated the association between the Ad-36 antibody and obesity. 8,9 Currently, little is known about the cellular and molecular mechanisms underlying Ad-36-induced obesity. Recently, Ad-36 E4 orf-1 was identified as a novel inducer of the rodent and human adipocyte differentiation process.…”
Section: Introductionmentioning
confidence: 99%